The difficult quest for an answer to low growth dilemma in Turkey: The channel of debt and productivity - Balcilar, Mehmet (International Economic Society ies@econ-society.org, 2012)
Turkey is the only founding member of the OECD that lagged behind western economies in terms of per capita GDP. Turkey's low growth has been a dilemma, because it reformed it is economy, adopted Western institutions, and achieved high capital deepening for several decades, yet it is growth record has been disappointing. This paper analyzes the relationship between public debt and productivity in Turkey and offers a possible explanation to the long standing dilemma. Using time series data over the period 1970-2008, the study obtains evidence of a significant and negative relationship between total public debt and productivity growth in Turkey. In terms of the specific channels through which high debt affects economic growth and the allocation of resources in Turkey, the study finds that high public debt harms growth mostly through its impact on total factor productivity (TFP) growth. Our results indicate that the indirect impact on growth through reduced investment proposed by the debt overhang theories is not significant for Turkey. High debt levels reduce TFP growth by directing resources to poor investments, reducing infrastructure and human capital investment that enhances private sector productivity, and delaying reforms. Our results indicate that on average high debt reduced TFP growth in Turkey by 2.59 percent per year. © International Economic Society.
Keywords: Growth; Total factor productivity; Turkey